PROBLEMATIKA PENGGUNAAN RAGAM BAHASA JURNALISTIK PADA MEDIA MASSA DAN IMPLIKASINYA TERHADAP PEMBINAAN BAHASA INDONESIA DI MASYARAKAT - Marliana, N Lia; Puryanto, Edi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2009)
Good print media are those prioritizing the writing quality. Although theyemphasize more on effectiveness, efficiency, and cost, they should take intoaccount of the writing quality, without violating the Indonesian language rules.Some violations found in journalistic writing include: (1) spelling and punctuationviolations, (2) grammatical violations, consisting of errors in syllable separation,morphological violations, and syntactic errors, (3) semantic violations, and (4)discourse violations. Other problems concern loanwords, namely foreign wordsthat are already popular in the community. The replacement of foreign wordsabsorbed into the Indonesian language with unavailable Indonesian equivalentsresults in difficulty.Keywords: journalistic language, mass media, language maintenance